MEMBANGUN SISTEM INFORMASI PERMINTAAN BARANG ATK PADA PT. BANK SYARIAH MANDIRI DENGAN METODOLOGI BERORIENTASI OBYEK - Sukmawijaya Sukmawijaya; Ita Novita (Universitas Budi Luhur, 2013)
In this globalization era, a company is in need of information services in a rapid, precise, accurate and relevant. The use of information technology as a tool in a variety of business processes will benefit operations in a company. PT. Bank Syariah Mandiri is one of financial institution that engages is Syariah is also required to provide prompt service both internal and external corporate. The problems that exist in PT. Bank Syariah Mandiri is that it is found some processes still done manually one of it is freight demand which is in the Division of Facilities and Logistics, both in recording, requests, orders, returns and preparing reports of stuff, so frequent delays and errors in manufacturing records and reports such as the difference between data with physical goods. To overcome these problems, is to made a system that can control the demand for goods such as administrative office materials. The purpose of this research is to design and build information systems office materials demand for good by using UML as a modelling technique system. The design of the proposed system will be implemented in PT. Bank Syariah Mandiri by using Microsoft Visual Sutio 2005 with the database used is MsSQL. Results from this study is a system design that can help process requests office materials goods become more effective and efficient, and can improve service to employees with more leverage.Keywords: Office materials, Information System, Unfied Modelling Language, PT. Bank Syariah Mandiri